Is the incidence of anaplastic thyroid cancer increasing: A population based epidemiology study - Tyler A. Janz (KeAi Communications Co., Ltd., 2019)
Objective: To provide an understanding of the incidence of anaplastic thyroid cancer within the United States. Methods: Patients in the Surveillance, Epidemiology, and End Results (SEER) database were included from 1973 to 2014 based on a diagnosis of anaplastic thyroid cancer using ICD O-3 codes. Patients were categorized into cohorts based on their year of diagnosis. Results: 1527 patients were diagnosed with anaplastic thyroid cancer within the SEER 18 registries. The age-adjusted incidence rate was 0.2 per 1,000,000 people (95% CI: 0.0–0.5) in 1973 and was 1.2 per 1,000,000 people (95% CI: 0.8–1.6) in 2014 (average annual percent change: 3.0% [95% CI: 2.2%–3.7%]). Patients tended to be of older age (mean age: 70.5 [range 15.0–102.0]), of female sex (62.8%), and Caucasian (81.1%). Finally, survival over time remained the same, as median disease specific survival months was 4.00 (95% CI: 2.26–5.74) from 1995 to 1999 and 4.00 (95% CI: 3.26–4.74) from 2010 to 2014. Conclusions: The incidence rate of anaplastic thyroid cancer has increased from 1973 to 2014. Interestingly, median survival in months did not greatly change overtime. Based on this increasing incidence, physicians must act appropriately to identify patients with anaplastic thyroid cancer as it possesses a high morbidity and mortality. Level of evidence: 4. Keywords: Anaplastic thyroid cancer, Thyroid cancer, Head and neck, Head and neck endocrine surgery, Head and neck oncology